Invisible transfers in Indian federalism - Rao, M. Govinda (1997)
In most federal countries, design of intergovernmental transfers does not take into account violation of horizontal equity due to invisible transfers. Such subterranean transfers can be significant and they occur due to inter-state tax exportation arising from the levy of resource based (as against residence based) taxes and subsidised loans given to the states by the central government and the public sector banking system. This study estimates the volume of invisible transfers due to subsidised lending to states in India and demonstrates that such transfers have significantly reduced the progressivity of explicit intergovernmental transfers. - Reproduced
Keywords: Federalism - India; Intergovernmental fiscal relations - India; Intergovernmental fiscal relations